2021
DOI: 10.3390/pathogens10080981
|View full text |Cite
|
Sign up to set email alerts
|

Alphavirus Virulence Determinants

Abstract: Alphaviruses are important pathogens that continue to cause outbreaks of disease in humans and animals worldwide. Diseases caused by alphavirus infections include acute symptoms of fever, rash, and nausea as well as chronic arthritis and severe-to-fatal conditions including myocarditis and encephalitis. Despite their prevalence and the significant public health threat they pose, there are currently no effective antiviral treatments or vaccines against alphaviruses. Various genetic determinants of alphavirus vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 133 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…This mechanism of immune evasion unique to EEEV and WEEV and the examples above emphasize the significance of small differences in sequences that may be overlooked in potential srRNA vectors that would otherwise be missed from in vitro experimentation. A recent in-depth review covered numerous known virulence determinants in the coding and non-coding regions of alphaviruses [ 44 ].…”
Section: Srrna Vector–host Cell Interactionsmentioning
confidence: 99%
“…This mechanism of immune evasion unique to EEEV and WEEV and the examples above emphasize the significance of small differences in sequences that may be overlooked in potential srRNA vectors that would otherwise be missed from in vitro experimentation. A recent in-depth review covered numerous known virulence determinants in the coding and non-coding regions of alphaviruses [ 44 ].…”
Section: Srrna Vector–host Cell Interactionsmentioning
confidence: 99%
“…For New World alphaviruses, such as VEEV and EEEV, the capsid protein is associated with IFN antagonism [11,132]. In EEEV, a region of the capsid between 55 and 75 amino acids is associated with inhibition of host gene expression and interferon sensitivity, whereas WEEV has a nucleocapsid arrangement targeting the PRR pathways downstream of IRF3 [133,134]. In contrast, a study on VEEV and SINV has shown that the suppression of IFN-β and ISG mRNA production in neuron cells is associated with structural protein of VEEV but nonstructural protein of SINV [135].…”
Section: Alphaviral Antagonism Of the Type I Ifn Systemmentioning
confidence: 99%
“…Importantly, CHIKV continues to emerge with a significant increase in CHIKV cases in South America in 2023, emphasizing the importance of further studying the mechanisms, transmission, and spread of CHIKV (9) (10). The alphavirus genome consists of two open reading frames, the first encoding 4 nonstructural proteins (nsP1-nsP4) and the latter encoding the structural proteins, including capsid, E3, 6K/TF, and the class II fusion glycoproteins E1 and E2 (11). Embedded in the virion membrane, the CHIKV E1 and E2 glycoproteins are essential in the early stages of receptor-mediated endocytosis.…”
Section: Introductionmentioning
confidence: 99%